Teaching literature in virtual worlds : immersive learning in English studies - Webb, Allen (New York : Routledge, 2012)
What are the realities and possibilities of utilizing on-line virtual worlds as teaching tools for specific literary works? Through engaging and surprising stories from classrooms where virtual worlds are in use, this book invites readers to understand and participate in this emerging and valuable pedagogy. It examines the experience of high school and college literature teachers involved in a pioneering project to develop virtual worlds for literary study, detailing how they created, utilized, and researched different immersive and interactive virtual reality environments to support the teach.
Includes bibliographical references and index.
Keywords: Educational technology. -- Study and teaching -- Technological innovations; Literature; Web-based instruction; Immersion method (Language teaching)